2018
DOI: 10.2174/1389202919666180330153316
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Copy Number Variants in Inherited Neuropathies

Abstract: The rapid development in the last 10-15 years of microarray technologies, such as oligonucleotide array Comparative Genomic Hybridization (CGH) and Single Nucleotide Polymorphisms (SNP) genotyping array, has improved the identification of fine chromosomal structural variants, ranging in length from kilobases (kb) to megabases (Mb), as an important cause of genetic differences among healthy individuals and also as disease-susceptibility and/or disease-causing factors. Structural genomic variations due to unbala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…14,17 Besides the common PMP22 rearrangements, pathogenic copy number variants are known in MPZ, GJB1, MFN2 (in compound heterozygous state with a second pathogenic mutation), NDRG1, GAN, and SEPT9. 32,33 More recently, a 78-kb duplication of chromosome 8q24.3 locus at chromosome Xq27.1 and a 1.35-Mb duplication of chromosome 7q36.3 were identified as the cause of CMTX3 and dHMN1, respectively. 32 Our study identified novel pathogenic copy number variants in FDG4 and SH3TC2 and suggest that implementation of NGS panels in a diagnostic setting will lead to an increased identification of structural variants in known CMT genes.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Besides the common PMP22 rearrangements, pathogenic copy number variants are known in MPZ, GJB1, MFN2 (in compound heterozygous state with a second pathogenic mutation), NDRG1, GAN, and SEPT9. 32,33 More recently, a 78-kb duplication of chromosome 8q24.3 locus at chromosome Xq27.1 and a 1.35-Mb duplication of chromosome 7q36.3 were identified as the cause of CMTX3 and dHMN1, respectively. 32 Our study identified novel pathogenic copy number variants in FDG4 and SH3TC2 and suggest that implementation of NGS panels in a diagnostic setting will lead to an increased identification of structural variants in known CMT genes.…”
Section: Discussionmentioning
confidence: 99%
“…G‐banded karyotype analysis of stained, dividing cells is useful for the detection of genetic abnormalities (large deletions, duplications, and translocations) of >5‐10 Mb in size, provided these changes cause a change in banding pattern or chromosome structure, but is unable to detect smaller microdeletions and microduplications (Lalani, 2017; Salpietro, Manole, Efthymiou, & Houlden, 2018). FISH, involving the use of fluorescently labeled probes that hybridize to cells in metaphase or interphase, allow for the detection of submicroscopic events below the level of detection of G‐banded karyotype analysis.…”
Section: Chromosomal Structural Variants (Insertions/deletions Duplimentioning
confidence: 99%
“…Locus‐specific probes vary in size based on the cloning vector used, ranging from 1‐10 kb in the case of plasmid vectors and 80 kb to 1 Mb in the case of P1‐derived artificial chromosome vectors (PAC), yeast artificial chromosome vectors (YAC) and bacterial artificial chromosome vectors (BAC) (Harada & Korf, 2013). FISH helps to specify the locus on a chromosome(s) and can determine copy number and help localize chromosomal segments detected on other platforms (e.g., microarray and NGS) (Salpietro et al., 2018).…”
Section: Chromosomal Structural Variants (Insertions/deletions Duplimentioning
confidence: 99%
See 1 more Smart Citation
“…SCNAs are generated by chromosomal rearrangement. Another important mechanism of SCNA influencing cancer progression is through the gene dosage effect (Harel and Lupski, 2018;Salpietro et al, 2018). For a gene in the region of SCNA, if its expression increases with amplification of the copy number and vice versa, this gene would be defined as dosage-sensitive gene.…”
Section: Introductionmentioning
confidence: 99%